Investigação da prática de Tai Chi Chuan entre idosos - Teixeira, Leandro Assis (2008)
This work sought to investigate the practice of Tai Chi Chuan among elderly people, based on their participation in open groups of health programs organized the municipality of Santo André, State of São Paulo, Brazil. In my experience as a teacher of Chinese martial arts, especially the Tai Chi Chuan, I noticed that in spite of being a Chinese millennial art, which encourages mental concentration and control of body movements, it performs a preventive action, reducing the effects of degenerative diseases and providing psychological welfare. Aging is, doubtless, a process of discoveries and transformations experienced in an orderly rhythm of facts. Physical activity can benefit people of all ages; it is especially important to elderly people health. The practice of Tai Chi Chuan develops physical and mental capacity so that the individual can have a long and healthy life. Thus, I attempted to transform a real situation that is close to me into an object of investigation and analysis. As a survey instrument of the quality-of-life profile, the SF36® Form was used (The Medical Outcomes Study: 36-Item Short Form Health Survey), translated and validated in Brazil by CICONELLI. This study did not intend to exhaust the subject of Tai Chi Chuan or the therapeutic techniques used during aging process but provide a new complementary view for health professionals. Thai Chi Chuan is a set of Chinese disciplinary exercises that seek harmony of body, mind and spirit